Karakteristik Klinis Pasien Ptosis Yang Telah Dilakukan Operasi Di Pusat Mata Nasional Rumah Sakit Mata Cicendo - Madyaputra, Faris Mufid; Kartiwa, Raden Angga; Dahlan, M Rinaldi; Boesoirie, Shanti Fitrianti (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2022)
Introduction Ptosis is a condition of abnormal upper eyelid position in the primary gaze resulting in a decrease palpebral fissure width. Comprehensive assessments including history taking, physical and thorough eye examination are essential to determine the diagnosis and to decide the most appropriate management of ptosis according to the underlying etiology. The surgical intervention used in ptosis patients is based on the result of the physical examination. Purpose To describe the clinical characteristic of ptosis patient whom underwent surgical intervention at National Eye Center Cicendo Eye Hospital. Methods A descriptive retrospective study was conducted from medical records of ptosis patient after surgical intervention at National Eye Center Cicendo Eye Hospital, from January 2018 to December 2020. Results A total of 91 patients were reviewed. The median age was 19 years old, gender dominated by women. Of these patients, 66 (72.5%) patients had congenital ptosis and unilateral in 80 (87.9%) cases. Results obtained severe ptosis was the highest in ptosis degree as for 72 (79.1%). In total, 58 (63.7%) patients having moderate levator function. Levator resection repair technique was the method of choice in 51 (56%) patients. Conclusion The most commonly found clinical characteristics in ptosis patients whom underwent surgical intervention was severe degree ptosis and congenital ptosis.